Women in the Western cultural tradition and the caricature of Islam as misogynistic - Hasan, Md. Mahmudul (Bangladesh Institute of Islamic Thought (BIIT), 2017)
Partly because of the Christian doctrine of Original Sin and partly because of a long patriarchal history in which women and men were not viewed equally, pre-twentieth-century Western culture was replete with misogynistic rhetoric and references. Many well-established European philosophers and writers with misogynistic tendencies are still highly regarded and their writings intensely studied. Their negative attitudes and male chauvinistic ideas apparently do not stand in their way of being admired and recognized as scholars. Ironically, turning a blind eye to the highly unacceptable portrayal of women in the European cultural tradition, many Western commentators seek to associate Islam with misogyny and that without adequate understanding of the religion. Given this backdrop, this study will discuss the misrepresentation of women in the Western cultural tradition in order to show the untenability of blaming Islam for gender inegalitarianism.